The Conductivity of AC, Loss Tangent, and Relative Permittivity for Composites of PVC Paste/Graphite Electrode Waste - Abdullah A. Hussain; AlJaberi, Forat Yasir; Feras N. Hasoon (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
The behavior of AC conductivity (σac), loss tangent (tan δ), and relative permittivity (ε′) for composites of PVC-P/graphite electrode waste (GEW) was investigated, and a qualitative explanation was provided as a function of PVC-P weight fractions (0, 5, 10, 15, 20, and 25) wt. percent, temperature (30-90) °C, and frequency (100Hz-2MHz). The behaviors of the composites’ ac. conductivity and impedance as a frequency function and temperature have been examined. The permittivity was shown to rise with increasing temperature (Tg). The relative permittivity increased as the GEW filler concentration increased and was highest in the low-frequency range; nevertheless decreased as the frequency increased.